Hubungan ketersediaan air dan aktivitas fotosintesis pada reaksi gelap terang: Pendekatan ilmiah dan nilai-nilai konservasi islam - Nazila, Rohmatun (Maliki Interdisciplinary Journal, 2026)
Photosynthesis is a fundamental process that determines the survival of plants and provides oxygen for all living things. This process is directly influenced by environmental conditions, especially the availability of water, which acts as an electron donor in light reactions and supports plant physiological regulation. Water also serves as a medium for transporting nutrients through the xylem, so an imbalance in its availability can inhibit photolysis, reduce ATP and NADPH production, close stomata, and decrease the efficiency of the dark reaction in the Calvin cycle. From an Islamic perspective, water is viewed as the primary source of life, as stated in QS. Al-Anbiya: 30, so its use must be done wisely, without excess, and without causing damage. Islamic conservation values such as the prohibition of israf, tabdzir, and the obligation to protect the environment align with the concept of sustainable water management in modern scientific studies. This article aims to analyze the relationship between water availability and photosynthetic activity during the light and dark reaction stages, while linking it to Islamic conservation principles Islam. The study results indicate that the integration of scientific understanding and Islamic ethical values provides a holistic framework for maintaining water sustainability and preserving the photosynthesis process as the main pillar of ecosystem balance. These findings emphasize that sustainable water management is not only important in terms of .